THE FLOW PATTERNS IN DOWNWARD GAS-LIQUID FLOW IN A VERTICAL PIPE WITH NON NEWTONIAN LIQUID - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Two-phase flow is a part of multi-phase flow that is distinguished on the basis of its flow phases (liquid-gas, solid-liquid, and gas-solid), flow directions (co-current and counter current), and pipe positions (vertical, horizontal, or inclined). A non-newtonian fluid is the fluid which does not follow the linear stress-strain relation. The objectives of this research are to investigate the characteristics of the flow (flow pattern) in a vertical pipe with 32 mm inside diameter, the visualization of the flow and the map of Generalized-Flow-Pattern. In downward two phase flow (gas-liquid) by using a non-Newtonian Liquid (aqueous carboxyl methyl cellulose CMC) as a liquid phase. The test was conducted at constant liquid velocity while varying gas velocity. The research has been carried out by using a transparent pipe (plexiglass) with a diameter of 32 mm, air and CMC of two different viscosities as working liquid. The flow pattern was examined at liquid velocity of 0.083 m/s to 0.49 m/s, where as air flow velocity from 0.59 m/s to 2.43 m/s. The present experiment has been conducted at air pressure of 1 ATM and room temperature of 25Â° C. The results of the stady reveal that the flow pattern is effected by the inlet used. By using smoothed inlet the flow patterns accurred in the squence of bubbles, slugs, and falling film. For CMC liquid with two different viscosities (0.02 and 0.145 N.s/m2), the flow pattern is affected by the viscosity. Based on the visualization results of this research it can be concluded that the